A Comparative Study of Low Cost International Flight Delays - เกตุรักษา เมธัส; บุษบา กมล (Thai Journal of Science and Technology, 2021)
This research aims to study and compare the overall outbound flight delays and to find out the appropriate departure delay time distribution. Secondary data in the research are the delay departure time of international airlines from 3 destinations. The flight from Don Mueang International Airport to (1) Kansai International Airport (Osaka) Japan, (2) Narita International Airport (Tokyo) Japan, and (3) Taoyuan International Airport (Taipei) Taiwan. The results show that airline delay time which greater than or equal to 6 hours occurs two times from Bangkok to Osaka route, one time from Bangkok to Tokyo route, and two times from Bangkok to Taipei route. In each destination, the average delay departure time of each airline differs significantly. The suitable of the international departure delay time distribution are Burr distribution and Burr (4P) distribution.